2017
DOI: 10.1093/brain/awx339
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline reduces chronic microglial activation after brain trauma but increases neurodegeneration

Abstract: Head injury survivors can develop neurodegeneration associated with persistent neuroinflammation, but whether the latter is harmful or beneficial is unclear. Scott et al. report that minocycline reduces neuroinflammation months and years after injury but increases a blood marker of neurodegeneration, suggesting that persistent neuroinflammation has reparative effects long after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 52 publications
(88 reference statements)
2
148
2
1
Order By: Relevance
“…While the anatomical basis for increased FA values is unknown, it may be explained by increased post 4 injury axonal sprouting, increased myelination, or gliosis ([55]). Notably, microglial activation along fiber tracts far from the infarct site was previously demonstrated using PET-MRI in stroke ([56]) and TBI ([57]) patients. In the current study we show that following single penetrating vessel occlusion microglia/macrophages migrate along the white matter tracts, accompanied by wide range structural reorganization, both of which were mediated by the fractalkine axis.…”
Section: Discussionmentioning
confidence: 93%
“…While the anatomical basis for increased FA values is unknown, it may be explained by increased post 4 injury axonal sprouting, increased myelination, or gliosis ([55]). Notably, microglial activation along fiber tracts far from the infarct site was previously demonstrated using PET-MRI in stroke ([56]) and TBI ([57]) patients. In the current study we show that following single penetrating vessel occlusion microglia/macrophages migrate along the white matter tracts, accompanied by wide range structural reorganization, both of which were mediated by the fractalkine axis.…”
Section: Discussionmentioning
confidence: 93%
“…The relationship between minocycline-sensitive microglial activation and neurodegeneration may, however, be complicated. Minocycline treatment in the traumatic brain injury study 61 was also associated with increased plasma levels of neurofilament light, considered a marker of neurodegeneration. The faster progression seen with minocycline in ALS 25 also suggests that some activated microglia might have a reparative function so that their inhibition could accelerate neurodegeneration.…”
Section: Chapter 3 Resultsmentioning
confidence: 98%
“…Minocycline is potentially neuroprotective through several anti-inflammatory processes (suppression of microglial proliferation and activation, reduced release of interleukins 1β and 6 and of tumour necrosis factor alpha, decreased chemokine expression and decreased activity of metalloproteases) as well as anti-apoptotic and anti-oxidant effects. [11][12][13][14][15][16][17] A study of 15 patients with traumatic brain injury found reduced microglial activation, as visualised with 11 C-PBR28 positron emission tomography (PET), 61 following 12 weeks of treatment with 200 mg of minocycline per day, indicating that the dose ranges used in the MADE trial can have a measurable effect on anti-inflammatory targets. The relationship between minocycline-sensitive microglial activation and neurodegeneration may, however, be complicated.…”
Section: Chapter 3 Resultsmentioning
confidence: 99%
“…The logical next step is to identify a multidimensional profile employing distinct classes of emerging technologies that convey diverse, complementary and independent information thereby enabling clinicians to achieve better characterization of patients with TBI and stratify risk more effectively. Such strategy is likely to provide a greatly expanded understanding of the pathogenesis and consequences of PET imaging has been used to assess early injury mechanisms (Bergsneider et al, 2001;Coles et al, 2004), recovery (Yamaki et al, 2018), long-term neural consequence (Barrio et al, 2015;Bodart et al, 2017;Lupi et al, 2011) and neural correlates of functional deficits (Buchsbaum et al, 2015;García-Panach et al, 2011;Komura et al, 2019;Nakashima et al, 2007;Spadoni et al, 2015) or interventions (Östberg et al, 2018;Scott et al, 2018).…”
Section: Integration Of Mri Data With Other Imaging Techniques and Nomentioning
confidence: 99%
“…[C-11] PiB PET has also demonstrated amyloid aggregation in msTBI (Hong et al, 2014;Scott et al, 2016), recapitulating the temporal pattern seen in post mortem findings, and demonstrating specific early striatal deposition not detected by autopsy studies. Finally, there are now tracers targeting activated microglia (Coughlin et al, 2015;Scott et al, 2018) which permit examination of the shifting balance between pro-and anti-inflammatory processes induced by microglial activation that allow for restoration rather than perpetuation of injury (Sandvig et al, 2018) and thus potentially improve TBI outcome. Combining PET and MRI data has a great potential to advance the understanding of the primary and secondary pathophysiological mechanisms in TBI and future efforts in our working group will be focused on this vital integration of data types.…”
Section: Integration Of Mri Data With Other Imaging Techniques and Nomentioning
confidence: 99%